STUDY OF PHYSICAL AND MECHANICAL PROPERTIES OF SEEDS OF DESERT FODDER PLANTS DRIED IN A VACUUM-DRYING PLANT - Б. А. Кушимов; Х. Х. Хайдаров (Journals Park Publishing, 2024)
The article discusses the features of seeds of forage grasses as an object of drying and provides an analysis of the physical and mechanical properties of seeds of desert forage plants. The names of the seeds of forage plants desert looking for phytomelioration pastures. Shows the recommended modes of the drying process the seeds of forage plants and selection of the most effective ones for use as a drying facility in drying facilities, as well as major technological properties as seed material drying.
Keywords: seeds, drying, physical and mechanical properties, desert forage plants, phytomelioration, pastures, regime, process, drying object, drying installations, technological properties of seeds.